Sarcina ventriculi as the potential cause of abomasal bloat - Schemm, T.J.; DeBey, B.M.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sarcina-like bacteria, possibly Sarcina ventriculi, have been seen upon histopathologic examination of the abomasums of calves that died of abomasal bloat. The ability of the organism to grow at a low pH and produce large amounts of gas suggests that it may be the cause of abomasal bloat.
Keywords: Beef; Abomasal bloat; Calves; Sarcina ventriculi